The Wealth, Health and Wellbeing of Ireland's Older People Before and During the Economic Crisis - Alan Barrett; Vincent O'Sullivan (Institute for the Study of Labor (IZA), 2013)
The economic crisis of 2008/9 was felt more acutely in Ireland relative to elsewhere and culminated in the international bailout in 2010. Given the economic collapse, Ireland provides an ideal case-study of the link between wealth collapses and movements in variables such as health and well-being. Using nationally-representative samples of older people collected before and during the crisis, we show that mean net assets fell by 45 percent between 2006/7 and 2012/13. In spite of this massive fall in wealth, measures of health and well-being remained broadly unchanged. However, expectations about future living standards became less optimistic. The results tend to support the findings of other recent studies that recessions do not have widespread negative effects on health and well-being.
Keywords: D31; J14; 330; recession; wealth; health; wellbeing